The 18th Annual Congress of the SA Heart Association coming in 2017 - Association, SA Heart (SA Heart Journal, 2017)
18th Annual Congress of the SA Heart Association: 9-12 November 2017, Sandton Convention centre, Johannesburg. Conference theme: Fundamentals to innovation.